Public spaces as hotspots of zoonotic gastrointestinal parasite transmission: evidence from small animal and soil surveillance in Malaysia - Low, Suey Yee; Gun, Sze Kee; Babatunde, Sadiq Mohammed; Syed Hussain, Sharifah Salmah; Wan Ahmad Kamil, Wan Nur Ismah; Omar, Abdul Rahman; Othman, Azalea Hani; Tengku Azizan, Tengku Rinalfi Putra; Moktar, Maizatul Akmal; Azman, Noraain; Tan, Yian Ming; Abdul Aziz, Nor Azlina (Springer Science and Business Media B.V., 2026)
Background: Public spaces such as parks and playgrounds offer social and ecological benefits to communities, but it might also pose public health risks. This epidemiological survey investigated the presence and risk factors of zoonotic parasites in faecal and soil samples collected from 60 public spaces across Kuala Lumpur and Selangor, Malaysia. Methods: Eggs, cysts and larvae of parasites were collected from 71 faecal and 300 soil samples using flotation-sedimentation techniques. Species identification was done using both morphological and conventional PCR. Results: A total of 71 faecal samples were collected, comprising 40 cat faeces and 31 dog faeces. Of these, 63 samples (88.7%) were positive for at least one intestinal parasite. The prevalence of parasite in cat faeces (95.0%, 38/40) was higher than dogs (80.7%, 25/31). Overall, six genera of parasites were detected in faecal samples. Cystoisospora spp. (62.0%) was the most prevalent, followed by hookworms (46.5%) and Giardia spp. (22.5%). Among the 33 faecal samples that tested positive for hookworms, Ancylostoma ceylanicum was the most common species (81.8%). Hookworm coinfections with Cystoisospora spp. were commonly detected in faecal samples (37.5%). Viability testing revealed that 37.7% of collected hookworm eggs and 74.6% of collected Toxocara eggs were viable. In soil samples, hookworm larvae were found in 28 out of the 300 samples, and 16 out of 60 sampling sites (26.7%). Hookworm burdens were significantly higher in rural areas and beaches. Risk factor analysis revealed that the presence of dustbin was associated with reduced hookworm infections (OR=0.075, 95% CI: 0.007–0.520) in dogs. Higher odds of hookworms were found in cat faeces (OR=4.961, 95% CI: 1.10–25.98) and soil (OR=5.77, 95% CI: 1.54–20.26) from residential parks. Notably, faecal-soil concordance was observed at 43.8% sampling sites, all located in residential parks. It highlights that these areas are potential active transmission hotspots. Conclusions: These findings provide essential information for public health officials to develop targeted interventions to reduce the risk of transmission of zoonotic parasites in public spaces.